Advancing Discovery Research in Nephrology in Canada: A Conference Report From the 2021 Molecules and Mechanisms Mediating Kidney Health and Disease (M3K) Scientific Meeting and Investigator Summit. (December 2022) - Burger, Dylan; Abdelrasoul, Amira; Alexander, R. Todd; Ballermann, Barbara; Bridgewater, Darren; Chan, John S. D.; Cunanan, Joanna; Cybulsky, Andrey V.; Gerarduzzi, Casimiro; Gunaratnam, Lakshman; Hartwig, Sunny; Kapus, Andras; et al.
Purpose of conference: New discoveries arising from investigations into fundamental aspects of kidney development and function in health and disease are critical to advancing kidney care. Scientific meetings focused specifically on fundamental biology of the kidney can facilitate interactions, support the development of collaborative groups, and accelerate translation of key findings. The Canadian fundamental kidney researcher community has lacked such a forum. On December 3 to 4, 2021, the first Molecules and Mechanisms Mediating Kidney Health and Disease (M3K) Scientific Meeting and Investigator Summit was held to address this gap with the goal of advancing fundamental kidney research nationally. The meeting was held virtually and was supported by a planning and dissemination grant from the Canadian Institutes of Health Research. Attendees included PhD scientists, nephrology clinician scientists, engineers, industry representatives, graduate students, medical residents, and fellows. Sources of information: This report was prepared from the scientific program, registration numbers, and details obtained from the online platform WHOVA, and summaries written by organizers and participants of the 2021 meeting. Methods: A 21-person team, consisting of the organizing committee members and participants from the meeting, was assembled. Key highlights of the meeting and future directions were identified and the team jointly assembled this report. Key findings: Participation in the meeting was strong, with more than 140 attendees across a range of disciplines. The program featured state-of-the-art presentations on diabetic nephropathy, the immune system, kidney development, and fibrosis, and was heavily focused on trainee presentations. The moderated "Investigator Summit" identified key barriers to research advancement and discussed strategies for overcoming them. These included establishment of a pan-Canadian fundamental kidney research network, development of key resources, cross-pollination with clinical nephrology, better reintegration into the Canadian Society of Nephrology, and further establishment of identity and knowledge translation. Limitations and implications: The 2021 M3K meeting represented a key first step in uniting fundamental kidney researchers in Canada. However, it was universally agreed that regular meetings were necessary to sustain this momentum. The proceedings of this meeting and future actions to sustain the M3K Scientific Meeting and Investigator Summit are presented in this article.